Childhood Obesity Is Associated With Increased Risk of Most Lower Extremity Fractures - Kessler, Jeff (Springer-Verlag, 2012)
BACKGROUND: A number of studies have found an increased risk of lower extremity injuries in obese patients. Most studies, however, are unable to provide stable population-based estimates based on the degree of obesity and few assess the risk pertaining to more detailed fracture location in the lower extremities. QUESTIONS/PURPOSES: We therefore investigated the relationship between obesity and lower extremity fractures in different age and fracture locations in a stable population. METHODS: This is a population-based, cross-sectional study from the electronic medical records of 913,178 patients aged 2 to 19 years. The body mass index (BMI) for each patient in the cohort was used to stratify patients into five weight classes (underweight, normal weight, overweight, moderate obesity, and extreme obesity) based on BMI for age. Records were assessed for the occurrence of lower extremity fractures for each cohort member. The associations among the five weight classes and specific lower extremity fractures were estimated using multiple logistic regression models and expressed with odds ratios (ORs) and 95% confidence intervals (CIs) using multivariate analysis to adjust for patient demographic variables. RESULTS: Overweight, moderately obese, and extremely obese patients all had an increased OR of fractures of the foot (OR, 1.14, 1.23, and 1.42, respectively, with 95% CI, 1.04–1.24, 1.12–1.35, and 1.26–1.61, respectively) along with the ankle, knee, and leg (OR, 1.27, 1.28, and 1.51, respectively, with 95% CI, 1.16–1.39, 1.15–1.42, and 1.33–1.72, respectively). The association was strongest in the 6- to 11-year-old age group. We found no association between increasing BMI and increased risk of fractures of the femur and hip. CONCLUSIONS: Increasing BMI is associated with increased odds of foot, ankle, leg, and knee fractures in children. LEVEL OF EVIDENCE: Level III, prognostic study. See Guidelines for Authors for a complete description of levels of evidence.